Contesting Intellectual Property Norms in Global Digital Economy - Marwa (Journal of World Trade Studies, 2022)
This study will analyze the dialectical interaction between the global South and North in redefining intellectual property (IP) norms in the digital era, specifically by situating them in norm contestation. The focus of research will be on Brazil and India on the one hand, while the United States and Japan on the other hand. These countries are chosen based on their significance in challenging and defending existing IP norms in various international fora, namely Joint Initiative on E-Commerce and G20. Drawing on constructivist theory, the study applies the concept of norm entrepreneurs and antipreneurs which are helpful in mapping out the different positions and strategies of these countries. The study will probe how Brazil and India, as norm entrepreneurs pursue a more flexible IP norm, while those of the antipreneurs, the U.S and Japan, seek more protective IP norms. Despite the uncertainties, these contestations provide opportunities for the global South to restructure the normative architecture of the intellectual property, though with limited success.